Efektivitas Pengembangan LKPD Fisika SMA/MA Berbasis Inquiry Training Untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik - Rumi Yuliska; Syafriani Syafriani; Ramli Ramli (JURNAL EKSAKTA PENDIDIKAN (JEP), 2020)
Effectiveness is the level of suitability and success in the use of inquiry training worksheets in the learning process. The purpose of this study is to investigate the effectiveness of a Student Worksheet. The subjects of this study were 28 students and 1 teacher. This type of data is primary data. The result of effectiveness is marked by an increase in knowledge competency with a gain score of 0.64 which is categorized as moderate. The assessment of attitudes competency average attainment of 84.88% and assessment of creative thinking abilities in the very creative category at the third meeting with an average of 81.19. It can be concluded that the Student Worksheet developed was effective.